(untitled) (Fiep Bulletin - online, 2024)
The objective of this work was to evaluate the psychomotor development of preschool children in a public school in the Nata district, located in Coclé, Republic of Panama. The work was done with 12 students out of a total of 25 students in a single grade level. Six tests were carried out using Jack Capon’s psychomotor test, but with the adaptation of Carrasco S, (1998). The tests consisted of: Identification of body parts, balance evaluation, jumping with one foot, obstacle course, catching the ball. In the study, it was observed that within the six tests that the test has, there are two tests (test IV and test V) in which the evaluated did not present greater complexity when executing them, however in the other four tests there were a few complications for certain children when performing them. Mostly in the tests that have to do with balance, which are tests II and III.